2019
DOI: 10.1002/mrc.4847
|View full text |Cite
|
Sign up to set email alerts
|

Effect of d‐psicose substitution on gelatin based soft candies: A TD‐NMR study

Abstract: Confectionary gels are considered as composite gel systems composed of high amount of sugar and gelling agent such as gelatin or starch. d‐Psicose is classified as a type of rare sugar, which is a C‐3 epimer of fructose and has 70% of the sweetness of sucrose with a caloric value of 0.39 kcal/g. Utilization of d‐psicose in food products is gaining particular interest due to its low caloric value. In this study, gelatin‐based soft candies were formulated, and the effect of d‐psicose substitution was explored on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 40 publications
(70 citation statements)
references
References 33 publications
6
63
1
Order By: Relevance
“…In addition to higher hardness values of soy protein containing gels, due to soy protein-pectin gelation, it was observed that addition of D-Allulose also increased the hardness values. This result was not expected since D-Allulose is not good at water binding, 18,28 thus gel matrix was supposed to have still free water which could also hinder the gelation ability of pectin. Considering HMP gel mechanism, sugar is usually added to dehydrate the system, so possible pectin-water interaction, which can result in weak gel structure is not expected.…”
Section: Hardnessmentioning
confidence: 97%
See 4 more Smart Citations
“…In addition to higher hardness values of soy protein containing gels, due to soy protein-pectin gelation, it was observed that addition of D-Allulose also increased the hardness values. This result was not expected since D-Allulose is not good at water binding, 18,28 thus gel matrix was supposed to have still free water which could also hinder the gelation ability of pectin. Considering HMP gel mechanism, sugar is usually added to dehydrate the system, so possible pectin-water interaction, which can result in weak gel structure is not expected.…”
Section: Hardnessmentioning
confidence: 97%
“…This result was not expected since in another study where similar experiments were conducted with gelatin-based candies, D-Allulose had more tendency to retard crystallization while sucrose did not. 18 Moreover, there were numerous studies showing that sucrose had a distinct crystal region and had tendency to crystallize easily. [33][34][35] The previous study conducted with starch, SPI, D-Allulose, and sucrose also showed that in starch gels, sucrose containing gels crystallized more than D-Allulose containing ones which was exactly the opposite of what was observed in this study.…”
Section: X-ray Diffractionmentioning
confidence: 99%
See 3 more Smart Citations